Rapid Determination of the Specificity Constant of Irreversible Inhibitors (kinact/KI) by Means of an Endpoint Competition Assay. Issue 47 (1st October 2015) - Miyahisa, Ikuo; Sameshima, Tomoya; Hixon, Mark S.
Abstract: Owing to their covalent target occupancy, irreversible inhibitors require low exposures and offer long duration, and their use thus represents a powerful strategy for achieving pharmacological efficacy. Importantly, the potency metric of irreversible inhibitors is k inact / K I not IC50 . A simple approach to measuring k inact / K I was developed that makes use of an irreversible probe for competitive assays run to completion against test compounds. In this system, the k inact / K I value of the test compound is equal to ( k inact / K I )probe ×[probe]/IC50 . The advantages of this method include simplicity, high throughput, and application to all target classes, and it only requires an in‐depth kinetic evaluation of the probe. Abstract : No going back : The potency metric of irreversible inhibitors is k inact / K I not IC50 . A simple approach was developed that makes use of an irreversible probe for competitive assays run to completion against test compounds. In this system, k inact / K I of the test compound is equal to ( k inact / K I )probe ×[probe]/IC50 . Advantages include simplicity, high throughput, and application to all target classes, and it only requires an in‐depth kinetic evaluation of the probe.